2015
DOI: 10.1007/s10552-015-0526-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood lipids and colorectal polyps: testing an etiologic hypothesis using phenotypic measurements and Mendelian randomization

Abstract: Purpose Studies linking cholesterol levels to the development of colorectal neoplasia are inconsistent, and Mendelian randomization has been suggested as a way to help avoid problems with confounding and reverse causation. Methods We genotyped individuals who received a colonoscopy at Group Health (1998–2007) for 96 of 102 single-nucleotide polymorphisms (SNPs) identified by the Global Lipids Genetics Consortium. Participants included 139 advanced adenoma cases, 518 non-advanced adenoma cases, 380 non-adenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Yang et al investigated the obesity and serum lipids in old Chinese people with colorectal polyps, and found that colorectal polyps were signi cantly associated with increased TC and TG levels [12]. Another study by Passarelli et al found that cholesterol levels were associated with advanced colorectal adenomas [22]. However, some studies found no association between TC levels and colorectal adenoma [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al investigated the obesity and serum lipids in old Chinese people with colorectal polyps, and found that colorectal polyps were signi cantly associated with increased TC and TG levels [12]. Another study by Passarelli et al found that cholesterol levels were associated with advanced colorectal adenomas [22]. However, some studies found no association between TC levels and colorectal adenoma [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomization is a technique used to determine the causal impact of a risk factor on an outcome from observational data using genetic variants. It has already been used to investigate associations between blood lipids and colorectal polyps 27 , coronary heart disease 28 , and prostate cancer 29 . In our study, using the Mendelian randomization approach, none of the lipid genetic scores for dyslipidemia analyzed was associated with CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…12 found a 13% higher prevalence of colorectal adenomas per increase in TG levels at colonoscopy, a 4% lower per increase in HDL and similar blood concentrations of LDL and TC. There are two studies based on Mendelian randomization to assess the causality of dyslipidemia and colorectal neoplasia 11,27 . Passarelli et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the patients with colorectal polyps, there are more male patients than females because colorectal polyps are closely related to intestinal cancer (1,2). In Gastroenterology, large intestine polyps are often diagnosed and their incidence rates are constantly increasing (3). When the growth and death of colorectal epithelial cells are out of balance, and a certain degree of abnormal surface mucosal hyperplasia occurs, intestinal polyps emerge (4).…”
Section: Introductionmentioning
confidence: 99%